The rise of modern police and the European state system from Metternich to the Second World War / Hsi-huey Liang. - Liang, Hsi-huey, 1929- (Cambridge University Press, 1992)
The Rise of the Modern Police and the European State System from Metternich to the Second World War re-examines the diplomatic history of Europe from the 1820s to World War II as a succession of mounting police problems linking the countries of the Continent through their growing dependency on one another for domestic order, security, and social progress. It culminates in the clash between the movement toward international police collaboration and the alternative of Continental police hegemony by one power, as attempted by Nazi Germany between the late 1930s and 1945. This book is the first comprehensive history of Continental police systems, especially in the context of political and diplomatic history.